Legitimnost in relevantnost - Peter, Mateja (Teorija in praksa, 2016)
Peace operations are more than just an activity of the United Nations (UN), they symbolise what the organisation stands for. This contribution analyses past and recent trends in UN peacekeeping. It sees its transformations as a reflection of changes in the global order and a sign of the organisation's legitimacy deficit. Major reforms of the UN and its peace operations are unlikely. The UN will therefore remain preoccupied with its own legitimacy and the relevance of its peace operations for contemporary conflicts. Parallel to this, we can expect the development of new ad hoc approaches to conflicts.
Keywords: Legitimacy (Political science); Legitimnost; Mirovne operacije; Organizacija združenih narodov; Peacekeeping; Uporaba sile (Mednarodno pravo); Use of force (International law)